Contribuições para os estudos computacionais de ressarcimento por danos elétricos: limites de suportabilidade e induções eletromagnéticas - Rezende, Paulo Henrique Oliveira (2016)
The Brazilian Agency ANEEL throughout the standard known as PRODIST's "Modulo 9 - Reimbursement of Electrical Damage" has been in existence for almost four years. However, the general guidelines are still generating many doubts and disagreements about the decision-making processes associated with the reimbursement of damages to electrical equipment installed in consumer units. This issue, given its social relevance, the commercial relationship between suppliers and consumers, and even the growing demand represents, at present, a subject of extreme importance. This subject has motivated a number of researches directed to better substantiate the processes of analysis, with emphasis to the relationship between causes and effects, classically called causal nexus. Notwithstanding the advances already made regarding the application for studies of the consistency or not of the requests, some specific questions still deserve development. Within this context, the present PhD thesis is inserted, which is directed to the improvement of the existing product, in the form of three contributions to the present state of the art. A first, associated with obtaining and validating a computational model for LED TVs, thus integrating a new device to the other products already contemplated in the application in question. A second, linked with new proposals the limits of supportability to the voltage and current of supply for white line equipment and LED television. These quantities are of utmost importance to the process of the correlation between causes and effects on the claimed devices. And a final contribution, aimed at establishing the bases for the inclusion of the phenomena attributed to the incidence of atmospheric discharges at points close to the electric networks and their electromagnetic inductions.